2011
DOI: 10.1038/ni.2031
|View full text |Cite
|
Sign up to set email alerts
|

The encephalitogenicity of TH17 cells is dependent on IL-1- and IL-23-induced production of the cytokine GM-CSF

Abstract: Interleukin 17 (IL-17)-producing helper T cells (TH17 cells) require exposure to IL-23 to become encephalitogenic, but the mechanism by which IL-23 promotes their pathogenicity is not known. Here we found that IL-23 induced production of the cytokine granulocyte macrophage colony-stimulating factor (GM-CSF) in TH17 cells and that GM-CSF played an essential role in their encephalitogenicity. Our findings identify a chief mechanism that underlies the important role of IL-23 in autoimmune diseases. IL-23 induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

47
1,012
5
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 939 publications
(1,087 citation statements)
references
References 44 publications
47
1,012
5
6
Order By: Relevance
“…In contrast, I-BET-762 potently suppressed the production of IL17, the signature cytokine of Th17 cells, yet had a surprisingly minor effect on inflammation induced by Th17 cells in vivo. One explanation stems from the fact that this adoptive transfer model has a strong requirement for the cytokine GM-CSF (11,14) in addition to the well-established proinflammatory cytokines, IFN-γ and IL-17 (20,21). There are at least two pathways described that drive GM-CSF expression in T cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, I-BET-762 potently suppressed the production of IL17, the signature cytokine of Th17 cells, yet had a surprisingly minor effect on inflammation induced by Th17 cells in vivo. One explanation stems from the fact that this adoptive transfer model has a strong requirement for the cytokine GM-CSF (11,14) in addition to the well-established proinflammatory cytokines, IFN-γ and IL-17 (20,21). There are at least two pathways described that drive GM-CSF expression in T cells.…”
Section: Discussionmentioning
confidence: 99%
“…of GM-CSF production (14), whereas El-Behi et al demonstrated that stimulation with IL-1β promoted GM-CSF production from T cells even in the absence of RORγt expression (11). One possible explanation for the differential effects of I-BET-762 on GM-CSF production by Th1 and Th17 cells could be that RORγt-dependent and -independent pathways of GM-CSF expression differ in their sensitivity to inhibition by I-BET.…”
Section: Discussionmentioning
confidence: 99%
“…Those mAbs that potently neutralize the biological activity of GM-CSF may be useful in treating inflammatory diseases (45) like arthritis (46) and multiple sclerosis (47)(48)(49). Anti-GM-CSF mAbs may treat juvenile myelomonocytic leukemias (50) and epithelial cancers, which secrete GM-CSF that suppresses the immune response against cancer (51,52).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in EAE, PD-1 signaling in CNS-specific helper T cells may inhibit their expansion and secretion of inflammatory cytokines (10)(11)(12). Recently, T-helper 17 (Th17) cells were shown to be involved in EAE by producing IL-17 and GM-CSF (20,21). Two reports showed that PD-1 −/− mice mount an augmented Th17 response to EAE induction (14,16).…”
mentioning
confidence: 99%